2005
DOI: 10.1063/1.1897827
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature ferromagnetism in pulsed-laser deposited epitaxial (Zn,Mn)O thin films: Effects of substrate temperature

Abstract: Mathews, S.; Joseph, B.; Sekhar, B.R.; and Roul, B.K., "High-temperature ferromagnetism in pulsed-laser deposited epitaxial (Zn,Mn)O thin films: Effects of substrate temperature" (2005). David Sellmyer Publications. 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Work by Pradhan et al indicated that Zn 1−x Mn x O films grown at a substrate temperature of 500 °C exhibited room temperature ferromagnetism and growths beyond 500 °C showed a decrease in the magnetization due to the formation of Mn-related clusters [11]. Furthermore, Cheng et [14].…”
Section: Introductionmentioning
confidence: 99%
“…Work by Pradhan et al indicated that Zn 1−x Mn x O films grown at a substrate temperature of 500 °C exhibited room temperature ferromagnetism and growths beyond 500 °C showed a decrease in the magnetization due to the formation of Mn-related clusters [11]. Furthermore, Cheng et [14].…”
Section: Introductionmentioning
confidence: 99%
“…The XRD results of high oxygen pressure growth are similar to our previous report in which a narrow FWHM was seen with increasing substrate temperature. 17 Apparently, the ͑002͒ peaks for the as-grown and annealed films at 600°C turn out to be a superposition of two peaks, one from ZnO and the other from Mn-doped ZnO. We argue that a small amount of Mn is incorporated into the Zn site and forms a minority phase.…”
mentioning
confidence: 72%
“…17,18 As-doped ZnO the films were in situ annealed in nitrogen for 5 min at 200°C. The resistivity of the p-type ZnMnO films is in the range of 1 -2 ⍀ cm with hole concentrations between ͑4-8͒ ϫ 10 17 cm −3 .…”
mentioning
confidence: 99%
“…It is observed that FWHM decreases significantly from 0.36 to 0. 26 as T s increases from 300 C to 400 C. 18 However, it is clear that the AZO peaks become more intense as the T s increases due to enhanced texturing of the films. On the contrary, FWHM bounces back to 0.30 , probably due to induced disorders caused by heavy Al doping or creations of Al 2 O 3 clusters.…”
Section: Methodsmentioning
confidence: 98%